Hayek, Local Information, and Commanding Heights : Decentralizing State-Owned Enterprises in China - Huang, Zhangkai; Li, Lixing; Ma, Guangrong; Xu, Lixin Colin (American Economic Association, 2017)
Hayek (1945) argues that local information is key to understanding the efficiency of alternative economic systems and whether production should be centralized or decentralized. The Chinese experience of decentralizing SOEs confirms this insight: when the distance to the government is farther, the SOE is more likely to be decentralized, and this distance-decentralization link is more pronounced with higher communication costs and greater firm-performance heterogeneity. However, when the Chinese central government oversees SOEs in strategic industries, the distance-decentralization link is muted. We also consider alternative agency-cost-based explanations, and do not find much support.